Effectiveness and Safety of Needle Medial Collateral Ligament Pie-Crusting in Total Knee Arthroplasty: A Cadaveric Study - Ohmori, Takaaki; Kabata, Tamon; Kajino, Yoshitomo; Takagi, Tomoharu; Tsuchiya, Hiroyuki (The Journal of Knee Surgery, 2018)
Medial collateral ligament (MCL) pie-crusting technique in total knee arthroplasty (TKA) is one of the methods of medial release. The effects and risks of blade pie-crusting have been reported in previous studies. However, only a few have reported the safety and efficacy of needle pie-crusting. In this cadaveric study, we quantitatively evaluated the amount of gap change by MCL needle pie-crusting. We investigated five knees of four fresh human cadavers and performed posterior-stabilized TKA. Only deep MCL release as the medial release was conducted. We punctured the MCL from the deep layer to the superficial layer using a 18 G needle in a 90-degree flexion position for 0, 10, 20, 50, 75, and 100 times. Medial and lateral gaps were measured accurately with a balancer at determined times in 0 and 90-degree flexion positions. Changes in medial and lateral gaps were not significant differences in flexion and extension position. However, in 90-degree flexion, medial gap changes were tended to be larger than lateral gap changes. A 0.6 mm additional medial release and a 0.2 mm additional lateral release were found per 10 times pie crust in flexion position (100 times, p: 0.08). However, large differences existed among the cases. Needle pie-crusting is safer than blade pie-crusting because of the small efficacy of one-time pie crust. MCL needle pie-crusting showed varied effects for each case. This result indicates the risk of relaxation of an unexpected gap. Caution should be taken when choosing between needle pie-crusting and blade pie-crusting.
Keywords: total knee arthroplasty; medial collateral ligament; needle pie-crusting; gap; cadaveric study